Bridging animal and clinical research during SARS-CoV-2 pandemic: A new-old challenge - Winkler, Martin Sebastian; Skirecki, Tomasz; Brunkhorst, Frank M.; Cajander, Sara; Cavaillon, Jean-Marc; Ferrer, Ricard; Flohé, Stefanie B.; García-Salido, Alberto; Giamarellos-Bourboulis, Evangelos J.; Girardis, Massimo; Kox, Matthijs; Lachmann, Gunnar; et al. (EBioMedicine, 2021)
Many milestones in medical history rest on animal modeling of human diseases. The SARS-CoV-2 pandemic has evoked a tremendous investigative effort primarily centered on clinical studies. However, several animal SARS-CoV-2/COVID-19 models have been developed and pre-clinical findings aimed at supporting clinical evidence rapidly emerge. In this review, we characterize the existing animal models exposing their relevance and limitations as well as outline their utility in COVID-19 drug and vaccine development. Concurrently, we summarize the status of clinical trial research and discuss the novel tactics utilized in the largest multi-center trials aiming to accelerate generation of reliable results that may subsequently shape COVID-19 clinical treatment practices. We also highlight areas of improvement for animal studies in order to elevate their translational utility. In pandemics, to optimize the use of strained resources in a short time-frame, optimizing and strengthening the synergy between the preclinical and clinical domains is pivotal.
Gesehen am 15.07.2021